SKETSA PENDIDIKAN MULTIKULTURAL DALAM AL-QUR’AN DAN AS-SUNNAH - Iwan Hermawan; Masykur Mansyur (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2021)
Multicultural education is learning habituation or culture regardless of differences in gender, social class, ethnicity, ethnicity, religion, and culture. Implicitly, the Al-Qur'an and Hadith mention multicultural education, among others, it is found in the Q.S. Al-Hujurat: 13 about tribes and nations, and Q.S. Ar-Rum: 22 about language and skin color. The topic of this research is a sketch of multicultural education contained in the Al-Qur'an and Sunnah which will be used as a basis for finding models and methods in multicultural education. A sketch here can be interpreted as a picture or painting that is still general and requires in-depth study to understand it completely.The method used in this research is a literature study, which tries to reveal by analyzing textually and contextually. Textual analysis is carried out by using several relevant interpretations and journals, while contextual analysis is the writer's understanding so that it forms a complete understanding. Based on the results of this analysis, multicultural education is to instill sympathy, respect, appreciation, and empathy for adherents of different religions and cultures.Therefore, to become a reference in implementing multicultural education, important components or elements in a system are needed to process the achievement of the expected goals, namely 1) Strengthening equality rather than differences, 2) Mutual trust and mutual understanding, 3) Tolerance of differences, 4) Discussing is not imposing an opinion.